2009
DOI: 10.1111/j.1479-8301.2009.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum amyloid β protein in young and elderly depression: a pilot study

Abstract: Background: Depression may increase the risk of developing Alzheimer's disease (AD). Recent large cohort studies have also shown that a low plasma amyloid b (Ab)-42 level combined with a high Ab40 level increases the risk of developing AD, suggesting plasma Ab42/40 ratio as useful for identifying risk of developing mild cognitive impairment and AD. Although several studies have examined Ab levels in the peripheral blood of elderly individuals with depression, results have been inconsistent. Furthermore, no res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 27 publications
(50 reference statements)
2
20
0
Order By: Relevance
“…Mean age of LLMD subjects in this cohort was 73.8±8.5 years and the sample was comprised of homebound elderly with multiple concomitant chronic diseases. Additionally, the same difference in Aβ40/Aβ42 ratio was found in a cross-sectional study on 60 Japanese inpatient young and old depressed subjects [80], in which serum Aβ40 levels were significantly higher in young depressed patients compared to young controls (<60 years) and the Aβ40/Aβ42 ratio was significantly higher in both young and elderly depressed (≥60 years) patients compared to non-depressed controls (mean age of LLMD: 68.2±5.6 years), although the Hamilton Rating Scale for Depression (HAM-D)[81] score did not correlate by itself with Aβ40, Aβ42 levels or Aβ40/42 ratio. These findings were replicated on a larger sample of 193 inpatient young (<40 years), middle age (≥40 to <65) and old depressed subjects (≥65) and 413 controls.…”
Section: Resultssupporting
confidence: 65%
“…Mean age of LLMD subjects in this cohort was 73.8±8.5 years and the sample was comprised of homebound elderly with multiple concomitant chronic diseases. Additionally, the same difference in Aβ40/Aβ42 ratio was found in a cross-sectional study on 60 Japanese inpatient young and old depressed subjects [80], in which serum Aβ40 levels were significantly higher in young depressed patients compared to young controls (<60 years) and the Aβ40/Aβ42 ratio was significantly higher in both young and elderly depressed (≥60 years) patients compared to non-depressed controls (mean age of LLMD: 68.2±5.6 years), although the Hamilton Rating Scale for Depression (HAM-D)[81] score did not correlate by itself with Aβ40, Aβ42 levels or Aβ40/42 ratio. These findings were replicated on a larger sample of 193 inpatient young (<40 years), middle age (≥40 to <65) and old depressed subjects (≥65) and 413 controls.…”
Section: Resultssupporting
confidence: 65%
“…Other studies evaluated the plasma levels of Aβ peptides. Most studies found a significant reduction of plasma Aβ 42 and increased Aβ 40 :Aβ 42 ratio in LLD; although non-significant results have also been reported (Sun et al , 2008; Baba et al , 2012; Benitez et al , 2009; Kita et al , 2009). …”
Section: Introductionmentioning
confidence: 96%
“…The plaques typically consist of 39–42 amino acid A fragments, and the plasma ratio of 42 and 40 amino acids long fragments (A42/A40) is suggested of being useful for identifying the risk of developing mild cognitive impairment and AD [2], [3]. Based on the classification of amino acids by Branden and Tooze [4], 25 amino acids out of the total 42 have hydrophobic side chains in A42.…”
Section: Introductionmentioning
confidence: 99%